Black coffee - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Research and coffee cultivation Special issue of the Plantations, recherche, développement journal, CIRAD, Montpellier, France, 2002. 156 pp. ISSN 1254-7670 Euro 23 (+ postage)